2014
DOI: 10.1186/1471-2458-14-787
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the burden of acute gastrointestinal illness in the community in Gansu Province, northwest China, 2012–2013

Abstract: BackgroundAcute gastrointestinal illness (AGI) imposes considerable social and economic burden on low and middle-income countries. This study aimed to estimate the occurrence, distribution, and burden of self-reported AGI in Gansu Province of northwest China, where economic growth rates have lagged far behind those of other regions in China and systematic studies to investigate the burden of AGI are still lacking.MethodsTwelve-month, retrospective face-to-face surveys were conducted in three sentinel sites bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…The monthly incidence of foodborne acute gastroenteritis recorded in the current study was 10.9%, which was higher than that reported in Italy (8.9%) [ 7 ], France (2.6%) [ 4 ], Japan (3.5%), Trinidad and Tobago (5.1%), and British Columbia, Canada (9.2%). In addition, the monthly incidence of foodborne acute gastroenteritis in the current study was greater than that previously reported in Jiangsu (4.4%) and Gansu (8.5%) [ 33 37 ] Provinces, China. Differences in illness prevalence may be related to exposure to risk factors, research design, and/or survey method.…”
Section: Discussioncontrasting
confidence: 84%
“…The monthly incidence of foodborne acute gastroenteritis recorded in the current study was 10.9%, which was higher than that reported in Italy (8.9%) [ 7 ], France (2.6%) [ 4 ], Japan (3.5%), Trinidad and Tobago (5.1%), and British Columbia, Canada (9.2%). In addition, the monthly incidence of foodborne acute gastroenteritis in the current study was greater than that previously reported in Jiangsu (4.4%) and Gansu (8.5%) [ 33 37 ] Provinces, China. Differences in illness prevalence may be related to exposure to risk factors, research design, and/or survey method.…”
Section: Discussioncontrasting
confidence: 84%
“…The few studies on attribution of intestinal disease from LMICs mainly rely on self-reporting on the cause of disease, which is not very reliable. However, they suggest acute gastro-intestinal disease is common (around one in two people a year) and around one third of cases (12%–55%) are self-attributed to food [ 41 , 42 , 43 , 44 ]. The WHO estimates that diarrhoeal diseases have a global burden of 99,727,954 DALYs and that 90% of these are the result of illness in lower income and lower middle-income countries [ 45 ].…”
Section: Review Findingsmentioning
confidence: 99%
“…Figure 4 (below) shows the foods implicated in FBD from three large, comprehensive national studies in the UK, USA and Netherlands, one small study in India, and one small, selfreported study from China (Painter et al, 2013;Sudershan et al, 2014;Mangen et al, 2014;Tam et al, 2012;Sang et al, 2014).…”
Section: Box 4: Polycyclic Aromatic Hydrocarbons In Fish -An Example mentioning
confidence: 99%
“…The studies that exist find acute gastro-intestinal disease is common (around one in two people a year) and around one third of cases (12-55%) were attributed to food (Bureau of Epidemiology, 2004;Ho et al, 2010;Chen et al, 2013;Sang et al, 2014 …”
Section: Dfid (Ceil Peaks)mentioning
confidence: 99%
See 1 more Smart Citation